PENGARUH RETURN ON EQUITY, CURRENT RATIO, DEBT TO EQUITY RATIO, & EARNING PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN TAMBANG SUB SEKTOR TAMBANG BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Maulina Putri Saraswati, Dwinda; Panjaitan, Fery; Shinta Lestari, Deara (Jurnal Ilmiah Niaga Bisnis Elektronik, 2022)
This research aims to determine the effect of Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), & Earning per Share (EPS) on Share Prices of Mining Companies in the Coal Mining Sub-Sector Listed on the Indonesia Stock Exchange in 2016-2020 either partially or simultaneously. The number of samples used in this study were 8 coal mining sub-sector companies listed on the Indonesia Stock Exchange from a total population of 28 companies. The type of data is secondary data sourced from the company's financial statements and annual reports. The data analysis method used is multiple linear regression analysis. The results of hypothesis testing in this research indicate that simultaneously Return on Equity (ROE), Current Ratio (CR), Debt to Equity Ratio (DER), & Earning per Share (EPS) have no significant effect on stock prices. Partially, Return on Equity (ROE) has an effect on stock prices. Meanwhile, Current Ratio (CR), Debt to Equity Ratio (DER), & Earning per Share (EPS) have no effect on stock prices.